2019
DOI: 10.15537/smj.2019.5.24080
|View full text |Cite
|
Sign up to set email alerts
|

Urological knowledge among primary health care physicians in Saudi Arabia

Abstract: Objectives: To evaluate the general knowledge among primary health care (PHC) physicians regarding the management of common urological problems in Saudi Arabia. Methods: This is an observational prospective study, where a self-administered questionnaire was distributed to practicing PHC physicians in the western region of Saudi Arabia on January 2017. The questionnaire consisted of 21-item questions, inquiring about demographics and general urological knowledge and skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several studies have already addressed the general public's poor awareness of LUTS' importance, as well as the awareness of GPs. [19][20][21]23,32,34 To our knowledge, we are the first to conduct a study on the importance of an educational interview with a GP on the recognition of LUTS, and the first to look for LUTS in the general population who were unaware of their condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have already addressed the general public's poor awareness of LUTS' importance, as well as the awareness of GPs. [19][20][21]23,32,34 To our knowledge, we are the first to conduct a study on the importance of an educational interview with a GP on the recognition of LUTS, and the first to look for LUTS in the general population who were unaware of their condition.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the connection of primary health care providers' level of education on LUTS and their ability to recognize LUTS in patients, as well as on the connection of patients' education on LUTS rehabilitation and their recovery rate. [19][20][21] Certain studies have assessed the connection between a person's educational level and the ability to evaluate the severity of LUTS using questionnaires in rural Africa, 22 or seeking medical help regarding incontinence in women. 23 Others have noted patients' educational level but have not linked it to the ability to assess the presence or severity of LUTS.…”
Section: Introductionmentioning
confidence: 99%
“…Now, there is the need to take care of health in order to keep disease away from the public quite effectively. In this study, the data was gathered from 200 people in order to assess how physiotherapists help the public to keep their health in the proper order [27]. They indicated that there is a positive correlation between the physiotherapists and primary healthcare and significantly improve the way of living of the people and contribute to managing all the health-related issues [28].…”
Section: Review Of Literaturementioning
confidence: 99%
“…The mixed research approach is the most suitable research approach for this research work because the data collection process of this study area lies in the category of qualitative research approach, and the data collection proves are lies in the category of the quantitative research approach. The different econometrics techniques are used for the analysis of the data because the collected data are in the qualitative form, and for the purpose of converting the qualitative data into a quantitative form, the data coding and the data cleaning are used for the analysis of the data [27].…”
Section: Research Approachmentioning
confidence: 99%